2008
DOI: 10.1016/j.neuroimage.2007.12.018
|View full text |Cite
|
Sign up to set email alerts
|

Motor-cortical beta oscillations are modulated by correctness of observed action

Abstract: Recent research has demonstrated that cortical motor areas are engaged when observing motor actions of others. However, little is known about the possible contribution of the motor system for evaluating the correctness of others' actions. To address this question we designed an MEG experiment in which subjects were executing and observing motor actions with and without errors. In the execution task subjects were asked to make speeded button presses according to instruction cues. During the observation task, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

26
129
2
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 171 publications
(158 citation statements)
references
References 46 publications
26
129
2
1
Order By: Relevance
“…This effect has been attributed to increased coactivation of MFC and motor cortices during feedback processing (Cohen and Ranganath, 2007). In turn, other studies reported stronger beta depression and rebound in MEG signals after error trials in a monitoring task (Koelewijn et al, 2008). Together with our results, this shows that the beta modulations are also sensitive to the errors in absence of motor responses.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…This effect has been attributed to increased coactivation of MFC and motor cortices during feedback processing (Cohen and Ranganath, 2007). In turn, other studies reported stronger beta depression and rebound in MEG signals after error trials in a monitoring task (Koelewijn et al, 2008). Together with our results, this shows that the beta modulations are also sensitive to the errors in absence of motor responses.…”
Section: Discussionsupporting
confidence: 86%
“…Together with our results, this shows that the beta modulations are also sensitive to the errors in absence of motor responses. Rather than reflecting low-level automatic motor resonance, the beta desynchronization corresponds to the discontinuation of the current cognitive states as a high level role, not restricted to motor related intentions (Koelewijn et al, 2008;van Schie et al, 2004). This study supports this theory, since no specific movement reaction is required in the task but the continuation of the cognitive state maintenance is no longer sustained after the perception of erroneous events.…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…Within cortex, the sensorimotor ␤-rhythm is classically thought to arise from motor, rather than somatosensory, regions (Brovelli et al 2002;Pfurtscheller et al 1997) and, therefore, has been mainly considered as a motor rhythm. In line with this, there is extensive evidence for a modulation of this rhythm by most aspects of movement: from movement execution (Jasper and Penfield 1949;Rougeul et al 1979), offset (Pfurtscheller et al 1997(Pfurtscheller et al , 1998, planning (Leocani et al 1997), preparation (Pfurtscheller et al 1998;Zhang et al 2008), inhibition (Pogosyan et al 2009;Swann et al 2009), and switching (Cheyne et al 2012;Gilbertson et al 2005;Stoffers et al 2001), to movement imagery (Brinkman et al 2014;Schnitzler et al 1997) and observation (Babiloni et al 2002;Koelewijn et al 2008;Orgs et al 2008, Pavlidou et al 2014. Furthermore, strong evidence for the motor function of the sensorimotor ␤-rhythm comes from the clear ␤-peak in the corticomuscular coherence: the coherence between the extracranial activity over the sensorimotor cortex and the EMG (Baker et al 1997;Salenius et al 1997).…”
Section: The Sensorimotor ␤-Rhythmmentioning
confidence: 67%
“…In fact, this rhythm does not seem to reflect a unitary phenomenon (Pfurtscheller et al., 65 1996;Pineda, 2005;Stancak and Pfurtscheller, 1995), but rather a combination of different 66 processes, potentially involved in the transformation of ''seeing'' into ''doing''. Moreover, a 67 complete overview of the spectro--temporal dynamics within the AON is missing, since many 68 studies in the literature considered only the alpha component (Kilner et al, 2006; Marshall et al., 69 2009;Pineda et al, 2000;Streltsova et al, 2010), or limited their 70 attention to the amplitude modulation of the oscillatory activity (Cochin et al, 1999; Hari et al., 71 1998; Kilner et al., 2009;Koelewijn et al, 2008; Orgs et 72 al., 2008), whereas studies on the temporal dynamics of brain activity during OBS and EXE focused 73 on the sensorimotor cortex only (Babiloni et al, 2002;Caetano et al, 2007). 74…”
mentioning
confidence: 99%